Lady or mermaid? An Essay on Ibsen’s “The Lady from the Sea” - Christensen, Arne (Wydawnictwo Naukowe UAM, 1992)
In the paper some aspects of Ibsen’s “The Lady from the Sea” are presented. The author discusses a radio version of the drama made by the Norwegian director Hans Heiberg, and compares it with Ibsen’s original text.